2007
DOI: 10.2223/jped.1727
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic rhinitis and its impact on the use of emergency care services in a group of children and adolescents with moderate to severe persistent asthma

Abstract: ResumoObjetivos: Avaliar a prevalência da rinite alérgica (RA) e os fatores associados à utilização de serviços de pronto-atendimento por asma aguda em crianças e adolescentes asmáticos tratados com corticóide inalatório. Métodos:Foi realizado um estudo transversal, do qual participaram 126 pacientes que se encontravam em tratamento com o dipropionato de beclometasona por 3 anos. Através de modelos de regressão logística, foram avaliados os fatores associados à consulta de pronto-atendimento no terceiro ano de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…(20) Studies have shown that rhinitis and asthma are interrelated, and that the appropriate treatment of allergic rhinitis improves asthma control, decreasing symptoms and reducing the risk of emergency room visits and hospitalizations. (21)(22)(23)(24)(25) Indeed, 35 children in the ProAR-FS with mild asthma (23.6% of the sample of children and adolescents) and persistent rhinitis, using exclusively nasal corticosteroid, were not hospitalized, and there was a decrease of 84.2% in the frequency of emergency room visits during monitoring in the ProAR-FS. Scientific evidence suggests that treatment of rhinitis with topical nasal corticosteroids prevents bronchial hyperresponsiveness associated with the exposure to allergens and can avoid the exacerbations of symptoms in patients with mild asthma.…”
Section: Resultsmentioning
confidence: 99%
“…(20) Studies have shown that rhinitis and asthma are interrelated, and that the appropriate treatment of allergic rhinitis improves asthma control, decreasing symptoms and reducing the risk of emergency room visits and hospitalizations. (21)(22)(23)(24)(25) Indeed, 35 children in the ProAR-FS with mild asthma (23.6% of the sample of children and adolescents) and persistent rhinitis, using exclusively nasal corticosteroid, were not hospitalized, and there was a decrease of 84.2% in the frequency of emergency room visits during monitoring in the ProAR-FS. Scientific evidence suggests that treatment of rhinitis with topical nasal corticosteroids prevents bronchial hyperresponsiveness associated with the exposure to allergens and can avoid the exacerbations of symptoms in patients with mild asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Allergic rhinitis also increases the risk of asthma hospitalization. In a cross-sectional study involving 126 asthmatic children and adolescents, the prevalence of AR was high and in combination with asthma severity constituted the major risk factor for emergency care attendance (43). Viral upper respiratory tract infection together with allergic sensitization and allergen exposure has been demonstrated to synergistically increase the risk of emergency care with asthma (44).…”
Section: Other Comorbiditiesmentioning
confidence: 99%
“…1 It is rarely observed as an isolated pathology, often being associated with asthma, [2][3][4][5] sinusitis, lymphoid tissue hypertrophy and obstructive sleep apnea. [2][3] There is a prevalence of 75 to 80% of asthma in patients who have allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3] There is a prevalence of 75 to 80% of asthma in patients who have allergic rhinitis. 5 Many of these patients also display mouth breathing. Rhinitis prevalence increases with age, 4,6 presenting wide variable values between countries and studies.…”
Section: Introductionmentioning
confidence: 99%